Exclusive Breastfeeding and Complementary Feeding Practices among Children in Slum of Pokhara - Sharma, Dibya; Kafle, Ramchandra (Journal of College of Medical Sciences-Nepal, 2020)
Background: It is estimated that, on an average about 35% of infants 0 - 6 months old are exclusively breastfed around the world. Optimal breastfeeding and complementary feeding practices can save the lives of 1.5 million children under five every year. The condition is further worse in slum areas where vulnerable group of people resides. So, this study aims to assess prevalence on initiation of breastfeeding, exclusive breastfeeding and complementary feeding practices. Methods: A cross sectional study was conducted from November 2017 - February 2018 among 400 married women having child between 6 - 24 months. A pre-tested structured questionnaire comprising of socio-demographic characteristics, exclusive breastfeeding and complementary feeding practice were used. Data was analyzed using Statistical Package for Social Sciences (SPSS) 18.0 version. Results: About 55% of the mothers had initiated breastfeeding within an hour (<1 hour). About half (50.5%) had practiced exclusive breastfeeding to their children. More than fifty percentages (51.5%)of the mothers introduced complementary foods at 6 months. Age at pregnancy, mode of delivery, family size and colostrum feeding is associated with early initiation of breastfeeding at 95% CI i.e. p value <0.05. Whereas, age of mother, ethnicity, mode of delivery and initiation of breastfeeding were significantly associated with exclusive breastfeeding at 95% CI i.e. p value <0.05. Conclusions: The breastfeeding and complementary feeding practice in slum area is not optimal. Health awareness program focusing on early initiation of breastfeeding, exclusive breastfeeding practices and timely introduction of complementary foods in these vulnerable groups of population is needed o prevent its untoward effects. Keywords: complementary feeding; exclusive breastfeeding; initiation; malnutrition.